2022
DOI: 10.3390/molecules27041194
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds from Pale Ale Beer Powder Attenuate Experimental Colitis in BALB/c Mice

Abstract: Phenolic compounds (PCs) present in foods are associated with a decreased risk of developing inflammatory diseases. The aim of this study was to extract and characterize PCs from craft beer powder and evaluate their potential benefits in an experimental model of inflammatory bowel disease (IBD). PCs were extracted and quantified from pure beer samples. BALB/c mice received either the beer phenolic extract (BPE) or beer powder fortified with phenolic extract (BPFPE) of PCs daily for 20 days by gavage. Colon sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…No morphological differences were observed between beetroot soup microparticles prepared at different ratios in starch or maltodextrin. The polysaccharide agents, however, modified microparticle morphology, with starch microcapsules presenting a spherical and irregular geometry with few surface depressions and aggregation formed by the adhesion of smaller particles to the surface of larger ones, in contrast to the maltodextrin microparticles, which presented a vitreous appearance, as described elsewhere [ 47 , 48 , 49 ]. Furthermore, no cracks or open pores were observed in either type of microparticle.…”
Section: Discussionmentioning
confidence: 73%
“…No morphological differences were observed between beetroot soup microparticles prepared at different ratios in starch or maltodextrin. The polysaccharide agents, however, modified microparticle morphology, with starch microcapsules presenting a spherical and irregular geometry with few surface depressions and aggregation formed by the adhesion of smaller particles to the surface of larger ones, in contrast to the maltodextrin microparticles, which presented a vitreous appearance, as described elsewhere [ 47 , 48 , 49 ]. Furthermore, no cracks or open pores were observed in either type of microparticle.…”
Section: Discussionmentioning
confidence: 73%
“…Inflammatory bowel disease (IBD) is common persistent incendiary infection, accompanied by a range of symptoms due to intestinal dysfunction, including diarrhea, rectal bleeding, abdominal pain and weight loss ( 1 , 2 ). The incidence of IBD has become a major health issue in recent years ( 3 , 4 ). Recent basic studies have identified risk factors for IBD that include malabsorption of selected nutrients ( 5 ) and the use of immunomodulators ( 6 ).…”
Section: Introductionmentioning
confidence: 99%